Expanding the Scope of Community Pharmacy Practice in Nova Scotia: Impacts on Provincial COVID-19 Response - Ingrid Sketris; Andrea Bishop; Tasha Ramsey; Jennifer Isenor; Chiranjeev Sanyal (McMaster University Library Press, 2023)
Nova Scotia has expanded the scope of practice for community pharmacists by allowing, among other changes, pharmacist prescribing under specific circumstances (2011) and administration of drugs by injection (2013), thereby alleviating stress on the health system. Due to these progressive expansions in community pharmacy scope of practice, Nova Scotia community pharmacy personnel (about 1,500 pharmacists and 246 technicians working in 315 pharmacies) were rapidly able to play key roles in the province's response to the COVID-19 pandemic. Community pharmacies provided medicines, medical devices, personal protective equipment, hand hygiene solutions, thermometers, and pulse oximeters to patients and the public. In addition, they have responded to patients' COVID-19-related needs by treating symptoms; providing referrals; discussing the benefits and risks of COVID-19 vaccines and administering them; making nirmatrelvir/ritonavir assessments; and addressing vaccine hesitancy and the spread of misinformation about COVID-19. Moreover, as in some other provinces, community pharmacists in Nova Scotia have played a leading role in delivering COVID-19 vaccines from almost the start of the vaccination campaign in December 2020. Their role expanded further in May 2022, when pharmacists were granted prescribing authority for inhaled budesonide in accordance with the provincial protocol to treat mild SARS-CoV-2 respiratory symptoms. La Nouvelle-Écosse a élargi le champ d'exercice des pharmaciens communautaires en autorisant, entre autres, la prescription par un pharmacien dans des circonstances spécifiques (2011) et l'administration de médicaments par injection (2013), soulageant ainsi le système de santé. Grâce à ces élargissements progressifs du champ d'exercice des pharmacies communautaires, le personnel des pharmacies communautaires de Nouvelle-Écosse (environ 1 500 pharmaciens et 246 techniciens travaillant dans 315 pharmacies) a pu contribuer de manière cruciale et rapide à la réponse de la province à la pandémie de COVID-19. Les pharmacies communautaires ont fourni des médicaments, des dispositifs médicaux, des équipements de protection individuelle, des solutions pour l'hygiène des mains, des thermomètres et des oxymètres de pouls aux patients et au public. En outre, elles ont répondu aux besoins des patients liés à la COVID-19 en traitant les symptômes, en orientant les patients, en discutant des avantages et des risques des vaccins contre la COVID-19 et de leur administration, en évaluant la pertinence de traiter certains patients au nirmatrelvir/ritonavir et en répondant à l'hésitation vaccinale et à la diffusion d'informations erronées sur la COVID-19. De plus, les pharmaciens communautaires de Nouvelle-Écosse, comme ceux d'autres provinces, ont joué un rôle de premier plan dans l'administration des vaccins contre la COVID-19 dès le début de la campagne de vaccination en décembre 2020. Leur rôle s'est encore élargi en mai 2022, lorsque les pharmaciens ont été autorisés à prescrire du budésonide inhalé, conformément au protocole provincial, pour traiter les symptômes respiratoires légers du SRAS-CoV-2.